Attack Stream Cipher By Using Cipher System Only - Hussein, K. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Attack  stream  cipher  system  , using cipher  text only  , depends on the  characteristics of  plain  teKt language  and  the randomness of  the key , that used  in encryption , without  having detailed  k.nuwh:dgt:: uf cipher algorithm by benefiting  from the balance between O's and  I' in the key to reduce the probability of key space.